2021
DOI: 10.3389/fpsyg.2021.622339
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Risk Factors Associated With Mental Health Symptoms Among the Outpatient Psychiatric Patients and Their Family Members in China During the Coronavirus Disease 2019 Pandemic

Abstract: Objective: To investigate the prevalence of and risk factors associated with mental health symptoms in psychiatric outpatients and their family members in China during the COVID-19 pandemic.Methods: This cross-sectional, survey-based, region-stratified study collected demographic data and mental health measurements for depression, anxiety and acute stress from 269 psychiatric patients and 231 family members in the Second Xiangya Hospital in China from April 27, 2020 to May 8, 2020. Binary logistic regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…For parents of special children, they had to take care and train children at home themselves, without professional help of rehabilitation institute (the kindergarten) and without adequate outdoor physical activity. In this situation, as common mental health influence factors, anxiety and sleep problems may occur more obviously (Qiu et al, 2021;Blasco-Lafarga et al, 2022). We have seen that social support will be the key point for solving anxiety and sleep disorders through their logical relationship in this study.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…For parents of special children, they had to take care and train children at home themselves, without professional help of rehabilitation institute (the kindergarten) and without adequate outdoor physical activity. In this situation, as common mental health influence factors, anxiety and sleep problems may occur more obviously (Qiu et al, 2021;Blasco-Lafarga et al, 2022). We have seen that social support will be the key point for solving anxiety and sleep disorders through their logical relationship in this study.…”
Section: Discussionmentioning
confidence: 69%
“…So, previous studies have found that anxiety, social support, coping style and sleep quality are related to each other. In addition, many studies have shown that the COVID-19 epidemic will affect individual sleep, anxiety and other mental health (Stanton et al, 2020;Qiu et al, 2021;Chatterjee, 2022). Studies have explored the psychometric relationship among these related variables, but the mediating role of social support and coping style between anxiety and sleep quality has been explored very rarely.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that SARS-CoV-2 infection increases the risk of anxiety and stress-related disorders, such as post-traumatic stress disorder (PTSD), leading to exacerbation of other psychiatric illnesses, including depression, bipolar disorder, schizophrenia, obsessive-compulsive disorder (OCD), substance abuse, and long-term cognitive decline [8][9][10][11][12][13][14]. Current studies have revealed high prevalence of depressive, anxiety, acute stress symptoms and increased COVID-19 related self-harm or suicidality in individuals with mental illness as well as an increased burden of nursing among their family members after the COVID-19 outbreak [15][16][17][18]. Moreover, patients in psychiatric institutes are more vulnerable to severe viral outbreaks because of their unclear movement trajectories before admission and low compliance to epidemic prevention measures like wearing masks after admission, easily leading to cluster infections in the wards [19].…”
Section: Introductionmentioning
confidence: 99%
“…A case-control study conducted by Fengyi et al revealed that psychiatric patients in China had higher mean Impact of Event Scale-Revised (IES-R); Depression, Anxiety and Stress Scale (DASS-21); and Insomnia Severity Index (ISI) scores than healthy controls during the early stage of the COVID-19 outbreak [37]. Recent studies targeting psychiatric patients with different backgroundsuch as age groups, occupations, and nationalities-revealed high proportion of patients suffering from depression, anxiety, and acute stress [38][39][40]. Patients also reported reduced quality of life in some studies [41,42].…”
Section: Introductionmentioning
confidence: 99%